The Effects of Gender and Family Wealth on Sexual Abuse of Adolescents - Eyglo Runarsdottir; Edward Smith; Arsaell Arnarsson (International Journal of Environmental Research and Public Health, 2019)
Background: Sexual abuse and sexual assaults against adolescents are among the most significant threats to their health and well-being. Some studies have found poverty to be a risk factor for sexual abuse. The present study investigates the effects of gender and family affluence on the prevalence of sexual abuse of 15-year-old Icelanders in the 10th grade. Methods: The study is based on data collected for the Icelandic part of the Health Behaviour in School-aged Children study in 2014. Standardized questionnaires were sent to all students in the 10th grade in Iceland, of which 3618 participated (85% of all registered students in this grade). Results: Girls were more than twice as likely to be sexually abused as boys (20.2% versus 9.1%). Adolescents perceiving their families to be less well off than others were twice as likely to report sexual abuse as those of ample or medium family affluence. However, family affluence had more effect on the prevalence of abuse in girls than in boys. Conclusion: Female gender and low socioeconomic status may independently contribute to the risk of sexual abuse.